Correlation between in vitro activity of milk leukocytes with milk constituents in high yielding crossbred cows - BURAGOHAIN, TRIPTI SHARMA; REDDY, SARATH CHANDRA; DAS, PRADIP KUMAR; GHOSH, PROBAL RANJAN; BANERJEE, DIPAK; MUKHERJEE, JOYDIP (The Indian Journal of Animal Sciences, 2017)
The relationship between the in vitro activity of milk leukocytes and milk constituents were studied in 48 high yielding clinically healthy crossbred cows. Milk somatic cell counts (SCC) was negatively correlated with milk lactose, total soid and solid not fat (SNF) content. Milk neutrophils were positively correlated with protein and Cu content and negatively correlated with fat content in milk. However milk lymphocytes were positively correlated with milk fat content and negatively correlated with protein content. Milk macrophages were positively correlated with milk SNF and total solid content. Milk lymphocyte blastogenic response (SI) was significantly positively correlated with milk protein, fat percentage and copper content and negatively correlated with milk lactose, milk total solids, SNF and zinc content. PI of milk neutrophils was positively correlated with zinc content and milk fat percentage and negatively correlated with milk total solid and SNF content. PI of milk macrophages was positively correlated with milk fat content. In the present investigation, immuno-potentiative role of various milk constituents such as milk protein, copper and zinc content on in vitro leukocyte activity was established.